Corporate Governance from a Post-Communist Perspective - Mihályi, Péter (Competitio, 2003)
In the aftermath of Enron and WorldCom scandals of 2001-2002, corporate governance (CG) has been put once again into the center of academic interest. Last time this happened in mid-1997, when a global financial crisis that began in Asia was widely attributed to appalling CG practices in Korea and Japan. Thus, for young readers this whole subject matter may seem to be an old hut. In reality, the term "corporate governance" has merely a 25 year old historiography. Systematic content analysis of the Anglo-Saxon press showed that the term CG arose first in the wake of the Watergate scandal. In the mid- to the late 1970s, public opinion suddenly discovered that major American corporations were involved in corrupt payments both at home and abroad. Prior to Wazergate scandal, competitive markets and good governance of business enterprises had been regarded as two sides of the same coin. It was a tacit understanding that well-run companies are honestly run companies and vice versa. Suddenly this equation was broken. Sence then the fast-growing CG literature has had a moral loading.